Perancangan Video Pariwisata Kawah Wurung Bondowoso Sebagai Media Promosi - Dwi Cahyaningtyas Mulyani; Pujiyanto Pujiyanto; Rina Nurfitri (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
Bondowoso is one of the regencies in Indonesia that has potential, including its natural tourism potential. Bondowoso is the only district in the â€œTapal Kudaâ€ area that does not have a coastline. Many potential tourism objects owned by Bondowoso Regency, one of which is "Wurung Crater". Therefore, the authors make promotional media in the form of videos that make about the tourism of Wurung Bondowoso Crater. The video was chosen because the video is a moving image that provides information on a concept and the message to be delivered. The best promotional media to get around are youtube and instagram. Videos provide convenience in terms of technical video making. The design model uses the Sadjiman Ebdi Sanyoto model, which begins with a background problem identification, data sources, then continues with the design concept, design process and final. The software used in the editing process includes: Adobe Premier pro CC 2015. The duration of this Wurung Crater video is around 1 minutes 20 seconds. Supporting media include t-shirts, hats, pins, books, stickers, x banners, bags, sleeping bags. For the next writer it is expected to be able to design with the same problems but with different media.